Analysis of Intention to Buy Cinema E-Tickets Among IPB Students with Theory of Planned Behavior (TPB) Approach - Tria Putri Simamora; Moh Djemdjem Djamaludin (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2020)
Internet technology has changed the way consumers buy products, one of which is the purchase of cinema tickets online (e-ticket). This study aimed to analyze of intention to purchase cinema e-tickets among IPB University students with the Theory of Planned Behavior (TPB) approach. This study used a cross-sectional study design and quantitative approach with online survey methods conducted at IPB campus. As many as 225 students were selected purposively as the research participant, with the criteria of undergraduate program students and had ever watched a movie at the cinema but had never bought a cinema e-ticket. The data analysis included descriptive analysis, reliability test, validity test, Spearmen correlation, and Structural Equation Model (SEM) using AMOS 21.0 and SPSS 25.0 programs. The results showed that age had a negative relationship with subjective norms, perceived behavioral control, and intention. The semester level also had a negative association with attitudes towards behavior, subjective norms, perceived behavioral control, and intention, whereas pocket money showed a negative relationship with subjective norms. The results of the analysis using SEM indicated that attitudes towards behavior, subjective norms, and perceived behavioral control had a significant positive effect on the intention to purchase cinema e-tickets. The perceived behavioral control variable had the most substantial influence on the purchase intention of cinema e-tickets, followed by subjective norms and attitudes towards behavior.